Evaluasi Usability Pada Get Hotel Rewards Berbasis Website Dengan Metode Post Study System Usability Questionnaire (PSSUQ) Dan Retrospective Think Aloud (RTA) - Suryani, Ni Kadek (Universitas Multi Data Palembang, 2025)
This study aims to evaluate the usability of the Get Hotel rewards website using the Post Study System Usability Questionnaire (PSSUQ) and Retrospective Think Aloud (RTA) methods. The usability evaluation was conducted to determine whether users find the website easy or difficult to use and whether the information provided is clear enough to prevent user difficulties. A mixed-method approach was employed, with quantitative data collect through the PSSUQ questionnaire involving 138 respondents, determined using the Lemeshow formula. Qualitative data were gathered through interviews using the RTA method, involving 10 selected respondents based on predetermined characteristics. The PSSUQ results showed average scores across four categories, SysUse at 1.82, InfoQual at 1.82, InterQual at 1,84 and Overall at 1,81, reflecting overall user satisfaction with the website. Meanwhile, the RTA method revealed several issues users encountered while using the website, along with suggestions for improving its functionality. Overall Get Hotel Rewards was deemed suitable for use and received positive feedback quantitatively. However, several aspects need improvement based on qualitative findings. According to respondents recommendations the proposed enhancements should address user challenges to improve the user experience and ensure the website meets higher usability standards in the future.